GEOLOGI DAERAH ALASON DAN SEKITARNYA, KECAMATAN RATATOTOK, KABUPATEN MINAHASA TENGGARA, SULAWESI UTARA - Najoan, A.D.; Masulili, F. (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2024)
Administratively, the research area is located in Ratatotok District, Minahasa Tenggara Regency, North Sulawesi. Geographically, the research area is situated at UTM (Universal Transverse Mercator) coordinates 51N between 687000-691000 meters easting and 98000-102000 meters northing, covering an area of 4 x 4 square kilometers (16 km²). The objective of this research is to understand the geomorphology, stratigraphy, geological structure, and geological history of the study area. The geomorphology of the research area consists of four geomorphological units: Karst hill unit, Karst plain unit, Intrusive hill unit, and Alluvial plain unit. The stratigraphy of the study area comprises three rock units arranged from oldest to youngest: Crystalline Limestone unit, Porphyritic Andesite unit, and Alluvial Deposit unit. The geological structure in the study area includes fractures oriented generally northwest to southeast and a suspected uplift fault. The geological history of the study area began in the early Miocene epoch with the deposition of the Crystalline Limestone unit, followed by the emplacement of hypabyssal intrusions forming the Porphyritic Andesite unit during the early to middle Miocene epoch. In the Holocene epoch, alluvial units were deposited non-conformably, accompanied by erosion processes shaping the morphology of the study area, which continue to the present day.